Strongly consistent estimation of all parameters in the Vasicek model by discrete observations - Приходько, О. Д.; Ральченко, К. В. (Київський національний університет імені Тараса Шевченка, 2022)
We construct estimators of all three unknown parameters in the Vasicek interest rate model based on discrete observations and prove their strong consistency. Theoretical results are illustrated by simulations. Pages of the article in the issue: 26 - 30 Language of the article: English

Побудовано оцiнки для всiх трьох невiдомих параметрiв у моделi Васiчека на основi дискретних спостережень та доведено їхню строгу конзистентнiсть. Теоретичнi результати проiлюстровано за допомогою моделювання.
Строго конзистентне оцiнювання всiх параметрiв моделi Васiчека за дискретними спостереженнями
Keywords: stochastic differential equation; interest rate model; low-frequency data; ergodic theorem; стохастичне диференцiальне рiвняння; модель вiдсоткової ставки; низькочастотнi данi; ерогодична теорема